A modelling framework to assess multiple metals impacts on marine food webs: Relevance for assessing the ecological implications of deep-sea mining based on a systematic review. (June 2023) - Martins, Irene; Guerra, Alexandra; Azevedo, Ana; Harasse, Ombéline; Colaço, Ana; Xavier, Joana; Caetano, Miguel; Carreiro-Silva, Marina; Martins, Inês; Neuparth, Teresa; Raimundo, Joana; Soares, Joana; et al.
Abstract: Industrial deep-sea mining will release plumes containing metals that may disperse over long distances; however, there is no general understanding of metal effects on marine ecosystems. Thus, we conducted a systematic review in search of models of metal effects on aquatic biota with the future perspective to support Environmental Risk Assessment (ERA) of deep-sea mining. According to results, the use of models to study metal effects is strongly biased towards freshwater species (83% freshwater versus 14% marine); Cu, Hg, Al, Ni, Pb, Cd and Zn are the best-studied metals, and most studies target few species rather than entire food webs. We argue that these limitations restrain ERA on marine ecosystems. To overcome this gap of knowledge, we suggest future research directions and propose a modelling framework to predict the effects of metals on marine food webs, which in our view is relevant for ERA of deep-sea mining. Highlights: There is a gap knowledge related to model metal effects on marine species. We present a framework that incorporates metal bioavailability, biokinetic and food web models (BA-BK-FW). The BA-BK-FW framework can predict metal effects on marine food webs. The BA-BK-FW will be useful for ERA (environmental risk assessment) of deep-sea mining.